Sistem Pengendali Sasaran Tembak DART (Disappear Automatically Retaliatory Target) Menggunakan Gelombang Radio - Ajulian Zahra, Ajub; Darjat, Darjat; Darpono, Rony (Transmisi, 2008)
As a citizen we have duty to keep our country in peace and safe, especially for military forces. Indonesian National Armed Forces keep the country safe an army needed to give a skill and proficiency for shooting. Because of that is necessary to willing a device for shooting practice, that is DART (Disappear Automatically Retaliatory Target). With this device hoped that military forces have many skills and proficiency as the way to keep the country in safety and peaceful from threat inside although outside of the country, so we can keep the united of the country. Beside this device can used by athlete as a shoot practice device that is can to increase achievement.In this final project we made control device of  DART (Disappear Automatically Retaliatory Target) that more familiar with shoot target, this shoot target can hide and appear as desire by used. This DART can give Retaliatory shoot when shooting on target is miss. The retaliatory is indicator lamp, this indicator lamp can be consider as retaliatory shoot to shooter because that target of shoot is miss. On the control device of  DART also completed with Hold using for repeat shoot.  Keyword : DART, Control system, Hold